Exploring the pressure–temperature behaviour of crystalline and plastic crystalline phases of N-isopropylpropionamide1. Issue 12 (28th March 2015) - Quesada-Cabrera, R.; Filinchuk, Y.; McMillan, P. F.; Nies, E.; Dmitriev, V.; Meersman, F.
<x xml:space="preserve">Abstract</x> The phase behaviour of crystalline and plastic crystalline phases of N-(isopropyl)propionamide (NiPPA) has been investigated by X-ray diffraction and a tentative P, T diagram has been constructed.